Skin and vitamin D: what degree of sun exposure is necessary to achieve the ideal serum level (Research, Society and Development, 2022)
Vitamin D is remembered in the literature for its great role in the body as a regulator of bone metabolism. However, in addition to its action on the osteoarticular system, its main effects extend to the skin, the endocrine system and the gastrointestinal tract. The main form of production of this vitamin occurs through its synthesis in the skin, when exposed to the sun. However, if done improperly, it can interfere with the benefits it brings to the body or even generate harmful effects. Therefore, it is essential to maintain appropriate levels of vitamin D, taking into account that each person responds differently to the stimulus of ultraviolet rays. Due to the many variables involved, such as time of exposure, exposure time, exposed skin area and skin color, the establishment of universal generic exposure standards that are supposedly adequate are debatable, implying that it is inevitable and essential to stipulate satisfactory degrees of sun exposure for each individual. individual, taking into account their particularities. Through meta-analysis, this work gathered relevant fragments of scientific articles related to vitamin D, and its cutaneous synthesis through ultraviolet rays, analyzing them, trying to conclude which are the ideal levels of sun exposure to meet the specific need for this vitamin for each group of individuals. The results found manifest as the main groups to perform the sun exposure women and caucasians. And, it was possible to portray the groups corresponding to age and phototype, being the most likely to individualization regarding the basic need for sun exposure to reach the essential serum level of vitamin D.